The Adaptive Management System for the Tasmanian Wilderness World Heritage Area — Linking Management Planning with Effectiveness Evaluation - Jones, Glenys (Adaptive Environmental Management, 2009)
This paper provides a 30 year retrospective on the development of the adaptive management system for the Tasmanian Wilderness World Heritage Area (Australia). It describes the historical background, key influences and stages that paved the way to establishment of adaptive management. It outlines how effectiveness monitoring, evaluation and reporting are integrated with the management plan for the Area to establish an ongoing adaptive management cycle. The chapter presents figures and tools for adaptive management, including 5 useful questions for guiding the integration of effectiveness monitoring, evaluation and reporting into management plans and programs. Strengths and weaknesses of the adaptive management system are discussed. Key lessons and insights distilled from this experience are offered, including the importance of planned monitoring of management effectiveness; the role of stakeholder assessments; and the factors that can assist in sustaining longterm strategic programs despite ongoing institutional change. The chapter concludes with suggestions for fostering an enabling environment for adaptive management.
Keywords: Adaptive Management; Management Intent; Reserve Management; World Heritage

Adaptive management of natural resources: theory, concepts, and management institutions. - Stankey, George H.; Clark, Roger N.; Bormann, Bernard T. (U.S. Department of Agriculture, Forest Service, Pacific Northwest Research Station, 2005)
This report reviews the extensive and growing literature on the concept and application of adaptive management. Adaptive management is a central element of the Northwest Forest Plan and there is a need for an informed understanding of the key theories, concepts, and frameworks upon which it is founded. Literature from a diverse range of ﬁelds including social learning, risk and uncertainty, and institutional analysis was reviewed, particularly as it related to application in an adaptive management context. The review identiﬁes opportunities as well as barriers that adaptive management faces. It concludes by describing steps that must be taken to implement adaptive management.

Adaptive Impact Management: An Integrative Approach to Wildlife Management - Riley, Shawn; Siemer, William; Decker, Daniel; Carpenter, Len; Organ, John; Berchielli, Louis (Human Dimensions of Wildlife, 2003)

Adaptive Management in Habitat Conservation Plans - Wilhere, George F. (Conservation Biology, 2002)
Habitat conservation plans (HCPs) allow incidental take of threatened or endangered species in exchange for conservation measures that minimize and mitigate such taking. Habitat conservation plans entail a compromise between regulatory certainty and scientific uncertainty. This compromise is controversial because many HCPs are thought to inadequately address scientific uncertainty. Adaptive management is the systematic acquisition and application of reliable information to improve natural resource management over time. Ideally, under adaptive management, conservation strategies are implemented as a deliberate experiment. This approach can establish cause-and-effect relationships and point the way toward optimal strategies. Adaptive management has been promoted as essential to management under uncertainty, but few HCPs incorporate genuine adaptive management. Habitat conservation plans will continue to lack adaptive management until certain conditions are met, such as acknowledgment that an HCP is a management hypothesis, landowner interest in improving biological outcomes, and sufficient financial resources. Economic incentives would encourage adaptive management in HCPs. Habitat conservation plan permittees might receive direct payments or tax deductions for reliable information that benefits a species. “Mitigation credits” could be awarded for information produced through adaptive management. In effect, habitat would be exchanged for information that benefits a species. Successful use of mitigation credits would depend on correctly valuing information and enforcement of the U.S. Endangered Species Act. Under a “precautionary polluter pays principle,” an HCP permittee would put up an environmental assurance bond. Portions of the bond are returned with interest as adaptive management demonstrates that environmental damages are unlikely to occur. Funds spent on adaptive management are funds unavailable for habitat protection, so limited financial resources may force a compromise between protecting habitat and acquiring knowledge.

Using Adaptive Management to Meet Conservation Goals - Franklin, Thomas M; Helinski, Ronald; Manale, Andrew (Fish and Wildlife Response to Farm Bill Conservation Practices, 2007)
Natural resource professionals should know whether or not they are doing an effective job of managing natural resources. Their decision-making process should produce the kind of results desired by the public, elected officials, and their agencies’ leadership. With billions of dollars spent each year on managing natural resources, accountability is more important than ever. Producing results is the key to success. Managers must have the necessary data to make enlightened decisions during program implementation—not just at the conclusion of a program. Adaptive management is described as an adapt-and-learn methodology as it pertains to implementing Farm Bill conservation practices. Four regional case studies describe how adaptive management is being applied by practicing fish and wildlife managers. Indicators were identified to monitor and evaluate contributions to fish and wildlife habitat for each of the case studies. Data collected at each stage of the studies were used to make mid-course adjustments that enabled leadership to improve or enhance ongoing management actions.

Adaptive Management: A Tool for Conservation Practitioners - Salafsky, Nick; Margoluis, Richard; Redford, Kent (Foundations of Success, 2001)

Adaptive Management, the Endangered Species Act, and the Institutional Challanges of New Age Environmental Protection - Doremus, Holly (Washburn Law Journal, 2001)

Calibrating conservation: new tools for measuring success - Kapos, Valerie; Balmford, Andrew; Aveling, Rosalind; Bubb, Philip; Carey, Peter; Entwistle, Abigail; Hopkins, John; Mulliken, Teresa; Safford, Roger; Stattersfield, Alison; Walpole, Matt; Manica, Andrea (Conservation Letters, 2008)
Conservation practitioners, policy makers, and donors agree that there is an urgent need to identify which conservation approaches are most likely to succeed in order to use more effectively the limited resources available for conservation. While recently developed standards of good practice in conservation are helpful, a framework for evaluation is needed that supports systematic analysis of conservation effectiveness. A conceptual framework and scorecard developed by the Cambridge Conservation Forum help to address common constraints to evaluating conservation success: unclear objectives, ineffective information management, the long time frames of conservation outcomes, scarcity of resources for evaluation, and lack of incentives for such evaluation. For seven major categories of conservation activity, the CCF tools help clarify conservation objectives and provide a standardized framework that is a useful basis for managing information about project outcomes and existing conservation experience. By identifying key outcomes that can predict conservation success and can be assessed in relatively short time frames, they help to make more efficient use of scarce monitoring and evaluation resources. With wide application, the CCF framework and evaluation tool can provide a powerful platform for drawing on the experience of past and ongoing conservation projects to identify quantitatively factors that contribute to conservation success.
Keywords: Conservation effect; Conservation outcomes; Evaluation; Evidence-based conservation; Monitoring; conservation impact; framework; indicators; scorecard